Will continuing liberalisation in the EC lead to instability in the EMS? - Wolfgang Schröder (Intereconomics, 1989)
The liberalisation of capital movements and the creation of a market without internal frontiers within the European Community have far-reaching consequences for the European Monetary System. Sr. Wolfgang Schröder analyses the opportunities and risks associated with these developments.
Keywords: 330; European Community